2001
DOI: 10.2337/diabetes.50.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Insulin Secretion in Children With Congenital Hyperinsulinism due to Sulfonylurea Receptor Mutations

Abstract: Mutations in the high-affinity sulfonylurea receptor (SUR)-1 cause one of the severe recessively inherited diffuse forms of congenital hyperinsulinism or, when associated with loss of heterozygosity, focal adenomatosis. We hypothesized that SUR1 mutations would render the ␤-cell insensitive to sulfonylureas and to glucose. Stimulated insulin responses were compared among eight patients with diffuse hyperinsulinism (two mutations), six carrier parents, and ten normal adults. In the patients with diffuse hyperin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 53 publications
9
98
0
4
Order By: Relevance
“…Although only limited data are available, there are reports that some CHI patients, even those non-surgically treated, can spontaneously progress to diabetes [7,48,49]. In addition, we have shown that normally hypersecreting Kir6.2[AAA] transgenic mice on a Kir6.2 +/− background (which, although untested, presumably have a greater reduction in K ATP channel activity than each genotype alone), but not Kir6.2 +/− mice, can progress from a hypersecreting phenotype to an undersecreting diabetic phenotype, when challenged by a highfat diet [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although only limited data are available, there are reports that some CHI patients, even those non-surgically treated, can spontaneously progress to diabetes [7,48,49]. In addition, we have shown that normally hypersecreting Kir6.2[AAA] transgenic mice on a Kir6.2 +/− background (which, although untested, presumably have a greater reduction in K ATP channel activity than each genotype alone), but not Kir6.2 +/− mice, can progress from a hypersecreting phenotype to an undersecreting diabetic phenotype, when challenged by a highfat diet [18].…”
Section: Discussionmentioning
confidence: 99%
“…A few PHHI cases have been examined in which there was no surgical treatment. In patients aged 11-13 years old, acute and prolonged insulin secretion were both suppressed, indicating that this progression can occur in untreated cases (18,27). In each of the previous genetic models of K ATP deficiency [in which beta cell K ATP currents are either completely absent (6, 7) or significantly reduced (5)], neonatal hyperinsulinemia and hypoglycemia very rapidly progressed to hyperglycemia with reduced glucoseinduced insulin secretion.…”
Section: Normal Islet Morphology Is Maintained In Kir62[aaa]mentioning
confidence: 99%
“…A second implication is that in humans with severe loss of K ATP channels, a progression from HI to glucose intolerance, as seen in K ATP channel KO mice [26][27][28]36], might be expected, either spontaneously or in response to dietary stress. Although only limited data are available, there are reports that some non-surgically treated patients with HI spontaneously progress to type 2 diabetes [11,20,56], that is onto the descending limb of the inverse U progression. The demonstration of reversibility of the process by removal of glibenclamide in mouse islets suggests the possibility that suppression of excitability with diazoxide, or dietary restriction, may prove beneficial in such patients.…”
Section: 'Inverse U' Model For B-cell Response To Hyperexcitabilitymentioning
confidence: 99%